Mutations in BRIP1 confer high risk of ovarian cancer - Rafnar, Thorunn; Gudbjartsson, Daniel F; Sulem, Patrick; Jonasdottir, Aslaug; Sigurdsson, Asgeir; Jonasdottir, Adalbjorg; Besenbacher, Soren; Lundin, Pär; Stacey, Simon N; Gudmundsson, Julius; Magnusson, Olafur T; le Roux, Louise; et al. (Nature genetics, 2011)
Using a combination of whole-genome sequencing, haplotype sharing and the genealogies of the Icelandic population, Thorunn Rafnar, Kari Stefansson and colleagues identified a rare coding mutation in the gene of a BRCA1-interacting factor, BRIP1 , that confers a high relative risk of ovarian cancer. Ovarian cancer causes more deaths than any other gynecologic malignancy in developed countries. Sixteen million sequence variants, identified through whole-genome sequencing of 457 Icelanders, were imputed to 41,675 Icelanders genotyped using SNP chips, as well as to their relatives. Sequence variants were tested for association with ovarian cancer ( N of affected individuals = 656). We discovered a rare (0.41% allelic frequency) frameshift mutation, c.2040_2041insTT, in the BRIP1 ( FANCJ ) gene that confers an increase in ovarian cancer risk (odds ratio (OR) = 8.13, P = 2.8 × 10 −14 ). The mutation was also associated with increased risk of cancer in general and reduced lifespan by 3.6 years. In a Spanish population, another frameshift mutation in BRIP1 , c.1702_1703del, was seen in 2 out of 144 subjects with ovarian cancer and 1 out of 1,780 control subjects ( P = 0.016). This allele was also associated with breast cancer (seen in 6/927 cases; P = 0.0079). Ovarian tumors from heterozygous carriers of the Icelandic mutation show loss of the wild-type allele, indicating that BRIP1 behaves like a classical tumor suppressor gene in ovarian cancer.